Photothermal bleaching in time-lapse photoacoustic microscopy - Gao, Liang (2012)
We studied the phenomenon of photothermal bleaching — a gradual reduction of contrast agent particles during repeated scans in photoacoustic microscopy. The dependence of the photothermal bleaching rate on the excitation pulse energy, pulse duration, and the absorber’s size was determined while the laser focal diameter was held constant. Our results showed that, the dependence of the photothermal bleaching rate on the excitation pulse energy differed before and after the absorbers were raised to their melting point by the deposited laser energy. Based on this finding, we suggested an optimal excitation pulse energy, which balances the photothermal bleaching rate and signal amplitude, for time-lapse imaging applications.